Reconstructing Honor Killing Through Siri’: A Cultural Perspective from Bugis-Makassar Society - Nur Fadhilah Mappaselleng; Zul Khaidir Kadir (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Honor killing within the Bugis-Makassar community cannot be fully understood through the lens of positive criminal law, as it is grounded in the normative system of siri’, which holds strong social legitimacy. This study addresses a gap in existing literature that overlooks local value systems as a source of normative justification for violence. It employs a qualitative method with a conceptual approach, using library research to explore siri’ as a regulatory structure. The findings reveal that siri’ positions collective honor above individual life, institutionalizing violence as a corrective obligation. The key contribution of this study is the introduction of cultural criminology as an alternative analytical framework to interpret violence legitimized by customary norms. These findings underscore the urgency of reforming criminal law to account for value pluralism within a legally plural society.